PENGARUH IMPLEMENTASI AIRPORT OPERATION CONTROL CENTER (AOCC) TERHADAP EFEKTIVITAS PELAYANAN DI BANDAR UDARA INTERNASIONAL SULTAN HASANUDDIN MAKASSAR - Sabila Fitri Prameswari; Arnaz Olieve; Didi Hariyanto (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
The Airport Operation Control Center (AOCC) is a room that is a place for collaboration with all stakeholders at the airport and functions as a command center for all airport activities. This study aims to determine whether there has been an increase in the effectiveness and efficiency of service performance for service users at Sultan Hasanuddin Airport Makassar since the implementation of AOCC. This study uses two independent variables, namely the implementation of AOCC as the independent variable and service effectiveness as the dependent variable. The sample of this research is employees who work in the internal unit of AOCC. Data was collected by distributing questionnaires to employees with a total of 50 respondents. The analytical method used is descriptive quantitative method. The results show that since the implementation of AOCC at Sultan Hasanuddin Airport Makassar, there has been an increase in the effectiveness and efficiency of services at Sultan Hasanuddin Airport Makassar, but some functions of the AOCC still need to be improved.